A low-pressure formation method for reducing the pressure rise time after hydration

Through the low-pressure transformation method of multi-stage transformation and gradient phosphoric acid treatment, the problem of poor hydration resistance of low-pressure transformation foil is solved, and the pressure boost time after hydration is significantly reduced and the hydration resistance is improved.

CN119145019BActive Publication Date: 2025-04-29NANTONG HAIXING ELECTRONICS +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411659058.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-04-29
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The existing low-pressure foils have poor hydration resistance, which leads to limited service life and reliability of aluminum electrolytic capacitors.

Method used

The low-pressure synthesis method of multi-stage synthesis and gradient phosphoric acid treatment is adopted, including multiple synthesis steps such as primary synthesis, secondary synthesis, and tertiary synthesis. The phosphoric acid solution at different concentrations is used for treatment in different steps, and finally heat treatment and drying is carried out at high temperature.

Benefits of technology

The boost time after hydration is significantly reduced and the hydration resistance of aluminum foil is improved, so that the boost time after 1 hour and 6 hours of hydration treatment is reduced by 60% and 40%, respectively.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the field of chemical foil technology, and in particular to a low-pressure chemical formation method for reducing the boost time after hydration. The low-pressure chemical formation method for reducing the boost time after hydration of the present invention comprises six-stage chemical formation, phosphoric acid treatment, post-treatment, phosphoric acid treatment, post-treatment, phosphoric acid treatment, heat treatment, and post-treatment. The anodized aluminum foil obtained by the chemical formation method of the present invention has improved capacity and hydration resistance, and the boost time after one-hour hydration treatment is reduced by about 60% compared with the original process, and the boost time after six-hour treatment is reduced by about 40% compared with the original process, thereby achieving a significant improvement in hydration resistance.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The invention relates to the technical field of chemically formed foils, in particular to a low-pressure chemically formed method for reducing the pressure rise time after hydration. Background Art

[0002] As an important raw material for aluminum electrolytic capacitors, low-voltage chemical foil has a wide range of applications in many fields. With the continuous advancement of technology and the optimization of processes, the performance of low-voltage chemical foil will be further improved. The current low-voltage chemical foil has been treated with special processes and has stable electrochemical properties. It can maintain good capacitance characteristics under various environments; compared with other types of capacitor materials, low-voltage chemical foil can provide greater capacitance, meet the needs of high energy density, and has advantages such as long service life. However, most of the current low-voltage chemical foil products have the problem of long hydration time. Hydration resistance is a key factor restricting the service life and reliability of aluminum electrolytic capacitors. The oxide film layer grown on the surface of the aluminum electrode foil serves as the working medium of the aluminum electrolytic capacitor. When working, it is directly in contact with the aqueous electrolyte. The water molecules in the electrolyte are adsorbed on the surface of the oxide film to form a hydrated aluminum oxide film, thereby destroying the insulating layer structure of the aluminum anodized film, resulting in a decrease in the dielectric properties of the electrode foil, an increase in the leakage current of the capacitor, and ultimately causing the aluminum electrolytic capacitor to fail, thus failing to meet the market demand for high-performance electrode foil.

[0003] Patent technology document CN202110402809.7 discloses a low-pressure chemical foil forming method and the low-pressure chemical foil obtained. Through the chemical forming method of the invention, the aluminum foil is formed in an aqueous adipate solution, washed with water, passivated in a phosphoric acid solution, and then heat treated and phosphorylated with a low concentration. The leakage current of the obtained low-pressure chemical foil is ≤14μF / cm 2 , which can effectively improve product stability. Although the invention can reduce its leakage current, it has not made practical research on its hydration resistance, which is bound to affect its use in actual situations. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a low-pressure forming method that reduces the pressure increase time after hydration, so as to solve the problem of poor hydration resistance of traditional forming foil.

[0005] Based on the above purpose, the present invention provides a low-pressure formation method for reducing the pressure rise time after hydration, comprising the following steps:

[0006] S1: The etched foil is subjected to primary chemical formation, secondary chemical formation, tertiary chemical formation, quaternary chemical formation, quinary chemical formation, and VI chemical formation in sequence;

[0007] S2: After the six-stage chemical foil is washed with water, it is placed in a phosphoric acid solution at 40-60°C for 60-180s. After washing with water, it is placed in a 2wt%-10wt% phosphate solution for the next treatment;

[0008] S3: washing the aluminum foil after the last treatment with water and placing it in a phosphoric acid solution at 40-60°C for 60-180s, and then placing it in a 2wt%-10wt% phosphate solution for the second treatment;

[0009] S4: washing the aluminum foil after the second treatment and placing it in a phosphoric acid solution at 40-60°C for 60-180s, and then heat treating it at 400-500°C for 80-180s.

[0010] S5: placing the heat-treated aluminum foil in a 2wt%-10wt% phosphate solution for the following three treatments, and then drying at 150-250° C. to obtain an anodized aluminum foil;

[0011] Further, the concentration of the phosphoric acid solution in step S2 is 18-25wt%;

[0012] Further, the concentration of the phosphoric acid solution in step S3 is 8-15wt%;

[0013] Furthermore, the concentration of the phosphoric acid solution in step S4 is 3-6wt%.

[0014] Furthermore, in step S1, the first-stage formation liquid is 1wt%-15wt% ammonium adipate solution, the second-stage formation liquid is 7wt%-15wt% ammonium adipate solution, the third-stage formation liquid is 5wt%-15wt% ammonium adipate solution, the fourth-stage formation liquid is 2wt%-10wt% ammonium adipate solution, the fifth-stage formation liquid is 2wt%-10wt% ammonium adipate solution, and the sixth-stage formation liquid is a mixed solution of ammonium adipate and phosphate; the temperature of the formation liquids is 60-80°C.

[0015] Furthermore, in the mixed solution of ammonium adipate and phosphate, the mass percentage of ammonium adipate is 2wt%-10wt%, and the mass percentage of phosphate is 1wt%-7wt%.

[0016] Furthermore, the primary formation time in step S1 is 5-10 min, and the current density is 0.10-0.30 A / dm 2 The secondary formation time is 5-15min, and the current density is 0.10-0.25A / dm 2 The time for the three-stage formation is 7-20 minutes, and the current density is 0.10-0.25A / dm 2 The time for the fourth stage formation is 7-20min, and the current density is 0.10-0.25A / dm 2 The five-stage formation time is 10-25min, and the current density is 0.10-0.25A / dm2 The six-stage formation time is 15-35min, and the current density is 0.10-0.15A / dm 2 .

[0017] Furthermore, the formation voltage is 20-200Vf.

[0018] Furthermore, the temperature of the latter treatment in step S2 is 70-90°C, the time is 5-15min, the voltage is 20-200Vf, and the current density is 0.05-0.15A / dm 2 .

[0019] Furthermore, the temperature of the second treatment in step S3 is 70-90°C, the time is 5-15min, the voltage is 20-200Vf, and the current density is 0.05-0.15A / dm 2 .

[0020] Furthermore, the temperature of the last three treatments in step S5 is 70-90°C, the time is 5-10 min, the voltage is 20-200 Vf, and the current density is 0.05-0.15 A / dm 2 .

[0021] Furthermore, the phosphate solution is one of ammonium dihydrogen phosphate solution, diammonium hydrogen phosphate solution, sodium dihydrogen phosphate solution, disodium hydrogen phosphate solution, potassium dihydrogen phosphate solution, and dipotassium hydrogen phosphate solution.

[0022] Beneficial effects of the present invention: The present invention adopts three phosphoric acid treatments in the post-treatment part of the original chemical formation process, and controls the concentration of the phosphoric acid solution to be gradually reduced during the phosphoric acid treatment, so that both the capacity and the hydration resistance of the finally obtained aluminum foil are improved, and the pressure rise time after one hour of hydration treatment is reduced by about 60% compared with the original process, and the pressure rise time after six hours of treatment is reduced by about 40% compared with the original process, thereby achieving a significant improvement in the hydration resistance. DETAILED DESCRIPTION

[0023] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0024] Example 1: (1) The corroded foil was placed in a 15wt% ammonium adipate solution for primary chemical treatment at a temperature of 80°C, a time of 5 min, a voltage of 20 Vf, and a current density of 0.10 A / dm 2 After washing, it was placed in a 10wt% ammonium adipate solution for secondary formation at a temperature of 80°C, a time of 5 min, a voltage of 25 Vf, and a current density of 0.10 A / dm 2After washing, it was placed in a 5wt% ammonium adipate solution for three-stage formation at a temperature of 80°C, a time of 10 min, a voltage of 45 Vf, and a current density of 0.25 A / dm 2 After washing, it was placed in a 2wt% ammonium adipate solution for four-stage formation at a temperature of 80°C, a time of 15 min, a voltage of 85 Vf, and a current density of 0.25 A / dm 2 After washing, it was placed in 2wt% ammonium adipate for five-stage formation at 80°C, 15min, 95Vf, and 0.25A / dm 2 After washing, it was placed in 1wt% ammonium adipate and 1wt% diammonium phosphate solution for six-stage formation at 80°C, 15min, 105Vf, and 0.15A / dm 2 ;

[0025] (2) After the sixth stage of chemical formation, the formed foil was washed with water and placed in a 18wt% phosphoric acid solution at a temperature of 60°C for 180s. After washing with water, it was placed in a 2wt% diammonium phosphate solution for the next treatment, wherein the temperature of the next treatment was 90°C, the time was 5min, the voltage was 105Vf, and the current density was 0.15A / dm 2 ;

[0026] (3) The aluminum foil after the second treatment was washed with water and placed in a 8wt% phosphoric acid solution at a temperature of 60°C for 180s. After washing with water, it was placed in a 2wt% diammonium phosphate solution for the second treatment. The temperature of the second treatment was 90°C, the time was 5min, the voltage was 105Vf, and the current density was 0.05A / dm 2 ;

[0027] (4) washing the aluminum foil after the second treatment with water, placing it in a 3wt% phosphoric acid solution at a temperature of 50°C for 180s, and then heat treating it at 450°C for 180s after washing with water;

[0028] (5) The aluminum foil after heat treatment was placed in a 2wt% ammonium dihydrogen phosphate solution for the following three treatments, and then dried at 150°C to obtain an anodized aluminum foil, wherein the temperature of the following three treatments was 90°C, the time was 5 min, the voltage was 105 Vf, and the current density was 0.05 A / dm 2 .

[0029] Example 2: (1) The corroded foil was placed in a 15wt% ammonium adipate solution for primary chemical treatment at a temperature of 80°C, a time of 5 min, a voltage of 20 Vf, and a current density of 0.10 A / dm 2 After washing, it was placed in a 10wt% ammonium adipate solution for secondary formation at a temperature of 80°C, a time of 5 min, a voltage of 25 Vf, and a current density of 0.10 A / dm2 After washing, it was placed in a 5wt% ammonium adipate solution for three-stage formation at a temperature of 80°C, a time of 10 min, a voltage of 45 Vf, and a current density of 0.25 A / dm 2 After washing, it was placed in a 2wt% ammonium adipate solution for four-stage formation at a temperature of 80°C, a time of 15 min, a voltage of 85 Vf, and a current density of 0.25 A / dm 2 After washing, it was placed in 2wt% ammonium adipate for five-stage formation at 80°C, 15min, 95Vf, and 0.25A / dm 2 After washing, it was placed in 1wt% ammonium adipate and 1wt% diammonium phosphate solution for six-stage formation at 80°C, 15min, 105Vf, and 0.15A / dm 2 ;

[0030] (2) After the sixth stage of chemical formation, the formed foil was washed with water and placed in a 22wt% phosphoric acid solution at a temperature of 50°C for 120s. After washing with water, it was placed in a 2wt% diammonium phosphate solution for the next treatment, wherein the temperature of the next treatment was 90°C, the time was 10min, the voltage was 105Vf, and the current density was 0.15A / dm 2 ;

[0031] (3) The aluminum foil after the second treatment was washed with water and placed in a 12wt% phosphoric acid solution at a temperature of 40°C for 120s. After washing with water, it was placed in a 2wt% diammonium phosphate solution for the second treatment. The temperature of the second treatment was 90°C, the time was 5min, the voltage was 105Vf, and the current density was 0.05A / dm 2 ;

[0032] (4) After washing the aluminum foil after the second treatment, place it in a 5wt% phosphoric acid solution at 50°C for 120s. After washing, heat treat it at 450°C for 130s.

[0033] (5) The aluminum foil after heat treatment was placed in a 2wt% diammonium phosphate solution for the following three treatments, and then dried at 200°C to obtain an anodized aluminum foil, wherein the temperature of the following three treatments was 90°C, the time was 8min, the voltage was 105Vf, and the current density was 0.05A / dm 2 .

[0034] Example 3: (1) The corroded foil was placed in a 15wt% ammonium adipate solution for primary chemical treatment at a temperature of 80°C, a time of 5 min, a voltage of 20 Vf, and a current density of 0.10 A / dm 2After washing, it was placed in a 10wt% ammonium adipate solution for secondary formation at a temperature of 80°C, a time of 5 min, a voltage of 25 Vf, and a current density of 0.10 A / dm 2 After washing, it was placed in a 5wt% ammonium adipate solution for three-stage formation at a temperature of 80°C, a time of 10 min, a voltage of 45 Vf, and a current density of 0.25 A / dm 2 After washing, it was placed in a 2wt% ammonium adipate solution for four-stage formation at a temperature of 80°C, a time of 15 min, a voltage of 85 Vf, and a current density of 0.25 A / dm 2 After washing, it was placed in 2wt% ammonium adipate for five-stage formation at 80°C, 15min, 95Vf, and 0.25A / dm 2 After washing, it was placed in 1wt% ammonium adipate and 1wt% diammonium phosphate solution for six-stage formation at 80°C, 15min, 105Vf, and 0.15A / dm 2 ;

[0035] (2) After the sixth-stage chemical formation, the formed foil was washed with water and placed in a 20wt% phosphoric acid solution at a temperature of 45°C for 110s. After washing with water, it was placed in a 2wt% diammonium phosphate solution for the next treatment, wherein the temperature of the next treatment was 90°C, the time was 8min, the voltage was 105Vf, and the current density was 0.15A / dm 2 ;

[0036] (3) The aluminum foil after the second treatment was washed with water and placed in a 10wt% phosphoric acid solution at a temperature of 60°C for 180s. After washing with water, it was placed in a 2wt% diammonium phosphate solution for the second treatment. The temperature of the second treatment was 90°C, the time was 15min, the voltage was 105Vf, and the current density was 0.05A / dm 2 ;

[0037] (4) After washing the aluminum foil after the second treatment, place it in a 6wt% phosphoric acid solution at 60°C for 130s. After washing, heat treat it at 500°C for 180s.

[0038] (5) The aluminum foil after heat treatment was placed in a 2wt% ammonium dihydrogen phosphate solution for the following three treatments, and then dried at 250°C to obtain an anodized aluminum foil, wherein the temperature of the following three treatments was 90°C, the time was 10 min, the voltage was 105 Vf, and the current density was 0.05 A / dm 2 .

[0039] Example 4: (1) The corroded foil was placed in a 15wt% ammonium adipate solution for primary chemical treatment at a temperature of 80°C, a time of 5 min, a voltage of 20 Vf, and a current density of 0.10 A / dm2 After washing, it was placed in a 10wt% ammonium adipate solution for secondary formation at a temperature of 80°C, a time of 5 min, a voltage of 25 Vf, and a current density of 0.10 A / dm 2 After washing, it was placed in a 5wt% ammonium adipate solution for three-stage formation at a temperature of 80°C, a time of 10 min, a voltage of 45 Vf, and a current density of 0.25 A / dm 2 After washing, it was placed in a 2wt% ammonium adipate solution for four-stage formation at a temperature of 80°C, a time of 15 min, a voltage of 85 Vf, and a current density of 0.25 A / dm 2 After washing, it was placed in 2wt% ammonium adipate for five-stage formation at 80°C, 15min, 95Vf, and 0.25A / dm 2 After washing, it was placed in 1wt% ammonium adipate and 1wt% diammonium phosphate solution for six-stage formation at 80°C, 15min, 105Vf, and 0.15A / dm 2 ;

[0040] (2) After the sixth-stage chemical formation, the formed foil was washed with water and placed in a 25wt% phosphoric acid solution at a temperature of 40°C for 180s. After washing with water, it was placed in a 2wt% diammonium phosphate solution for the next treatment, wherein the temperature of the next treatment was 90°C, the time was 15min, the voltage was 105Vf, and the current density was 0.15A / dm 2 ;

[0041] (3) The aluminum foil after the second treatment was washed with water and placed in a 15wt% phosphoric acid solution at a temperature of 55°C for 160s. After washing with water, it was placed in a 2wt% diammonium phosphate solution for the second treatment. The temperature of the second treatment was 90°C, the time was 15min, the voltage was 105Vf, and the current density was 0.05A / dm 2 ;

[0042] (4) After washing the aluminum foil after the second treatment, place it in a 6wt% phosphoric acid solution at 40°C for 60 seconds, and after washing, heat treat it at 500°C for 80 seconds;

[0043] (5) The aluminum foil after heat treatment was placed in a 10wt% ammonium dihydrogen phosphate solution for the following three treatments, and then dried at 250°C to obtain an anodized aluminum foil, wherein the temperature of the following three treatments was 90°C, the time was 5min, the voltage was 105Vf, and the current density was 0.05A / dm 2 .

[0044] Comparative Example 1: The difference from Example 2 is that only the phosphoric acid treatment in step (2) is performed, and the remaining steps are the same as Example 2. The specific steps are as follows:

[0045] (1) The corroded foil was placed in a 15wt% ammonium adipate solution for primary chemical treatment at a temperature of 80°C, a time of 5 min, a voltage of 20 Vf, and a current density of 0.10 A / dm 2 After washing, it was placed in a 10wt% ammonium adipate solution for secondary formation at a temperature of 80°C, a time of 5 min, a voltage of 25 Vf, and a current density of 0.10 A / dm 2 After washing, it was placed in a 5wt% ammonium adipate solution for three-stage formation at a temperature of 80°C, a time of 10 min, a voltage of 45 Vf, and a current density of 0.25 A / dm 2 After washing, it was placed in a 2wt% ammonium adipate solution for four-stage formation at a temperature of 80°C, a time of 15 min, a voltage of 85 Vf, and a current density of 0.25 A / dm 2 After washing, it was placed in 2wt% ammonium adipate for five-stage formation at 80°C, 15min, 95Vf, and 0.25A / dm 2 After washing, it was placed in 1wt% ammonium adipate and 1wt% diammonium phosphate solution for six-stage formation at 80°C, 15min, 105Vf, and 0.15A / dm 2 ;

[0046] (2) After the sixth stage of chemical formation, the formed foil was washed with water and placed in a 22wt% phosphoric acid solution at a temperature of 50°C for 120s. After washing with water, it was placed in a 2wt% diammonium phosphate solution for the next treatment, wherein the temperature of the next treatment was 90°C, the time was 10min, the voltage was 105Vf, and the current density was 0.15A / dm 2 ;

[0047] (3) The aluminum foil after the second treatment was washed with water and then placed in a 2wt% diammonium phosphate solution for the second treatment, wherein the temperature of the second treatment was 90°C, the time was 5 min, the voltage was 105 Vf, and the current density was 0.05 A / dm 2 ;

[0048] (4) After washing the aluminum foil after the second treatment, heat treat it at 450°C for 130s;

[0049] (5) The aluminum foil after heat treatment was placed in a 2wt% diammonium phosphate solution for the following three treatments, and then dried at 200°C to obtain an anodized aluminum foil, wherein the temperature of the following three treatments was 90°C, the time was 8min, the voltage was 105Vf, and the current density was 0.05A / dm 2 .

[0050] Comparative Example 2: The difference from Example 2 is that the phosphoric acid treatment in step (4) is not performed, and the remaining steps are the same as Example 2. The specific steps are as follows:

[0051] (1) The corroded foil was placed in a 15wt% ammonium adipate solution for primary chemical treatment at a temperature of 80°C, a time of 5 min, a voltage of 20 Vf, and a current density of 0.10 A / dm 2 After washing, it was placed in a 10wt% ammonium adipate solution for secondary formation at a temperature of 80°C, a time of 5 min, a voltage of 25 Vf, and a current density of 0.10 A / dm 2 After washing, it was placed in a 5wt% ammonium adipate solution for three-stage formation at a temperature of 80°C, a time of 10 min, a voltage of 45 Vf, and a current density of 0.25 A / dm 2 After washing, it was placed in a 2wt% ammonium adipate solution for four-stage formation at a temperature of 80°C, a time of 15 min, a voltage of 85 Vf, and a current density of 0.25 A / dm 2 After washing, it was placed in 2wt% ammonium adipate for five-stage formation at 80°C, 15min, 95Vf, and 0.25A / dm 2 After washing, it was placed in 1wt% ammonium adipate and 1wt% diammonium phosphate solution for six-stage formation at 80°C, 15min, 105Vf, and 0.15A / dm 2 ;

[0052] (2) After the sixth stage of chemical formation, the formed foil was washed with water and placed in a 22wt% phosphoric acid solution at a temperature of 50°C for 120s. After washing with water, it was placed in a 2wt% diammonium phosphate solution for the next treatment, wherein the temperature of the next treatment was 90°C, the time was 10min, the voltage was 105Vf, and the current density was 0.15A / dm 2 ;

[0053] (3) The aluminum foil after the second treatment was washed with water and placed in a 12wt% phosphoric acid solution at a temperature of 40°C for 120s. After washing with water, it was placed in a 2wt% diammonium phosphate solution for the second treatment. The temperature of the second treatment was 90°C, the time was 5min, the voltage was 105Vf, and the current density was 0.05A / dm 2 ;

[0054] (4) After washing the aluminum foil after the second treatment, heat treat it at 450°C for 130s;

[0055] (5) The aluminum foil after heat treatment was placed in a 2wt% diammonium phosphate solution for the following three treatments, and then dried at 200°C to obtain an anodized aluminum foil, wherein the temperature of the following three treatments was 90°C, the time was 8min, the voltage was 105Vf, and the current density was 0.05A / dm 2 .

[0056] Comparative Example 3: The difference from Example 2 is that the concentration of the phosphoric acid solution is 10 wt % during each phosphoric acid treatment, and the remaining steps are the same as Example 2. The specific steps are as follows:

[0057] (1) The corroded foil was placed in a 15wt% ammonium adipate solution for primary chemical treatment at a temperature of 80°C, a time of 5 min, a voltage of 20 Vf, and a current density of 0.10 A / dm 2 After washing, it was placed in a 10wt% ammonium adipate solution for secondary formation at a temperature of 80°C, a time of 5 min, a voltage of 25 Vf, and a current density of 0.10 A / dm 2 After washing, it was placed in a 5wt% ammonium adipate solution for three-stage formation at a temperature of 80°C, a time of 10 min, a voltage of 45 Vf, and a current density of 0.25 A / dm 2 After washing, it was placed in a 2wt% ammonium adipate solution for four-stage formation at a temperature of 80°C, a time of 15 min, a voltage of 85 Vf, and a current density of 0.25 A / dm 2 After washing, it was placed in 2wt% ammonium adipate for five-stage formation at 80°C, 15min, 95Vf, and 0.25A / dm 2 After washing, it was placed in 1wt% ammonium adipate and 1wt% diammonium phosphate solution for six-stage formation at 80°C, 15min, 105Vf, and 0.15A / dm 2 ;

[0058] (2) After the sixth-stage chemical formation, the formed foil was washed with water and placed in a 10wt% phosphoric acid solution at a temperature of 50°C for 120s. After washing with water, it was placed in a 2wt% diammonium phosphate solution for the next treatment, wherein the temperature of the next treatment was 90°C, the time was 10min, the voltage was 105Vf, and the current density was 0.15A / dm2;

[0059] (3) After washing the aluminum foil after the second treatment, place it in a 10wt% phosphoric acid solution at a temperature of 40°C for 120s. After washing, place it in a 2wt% diammonium phosphate solution for the second treatment, wherein the temperature of the second treatment is 90°C, the time is 5min, the voltage is 105Vf, and the current density is 0.05A / dm2;

[0060] (4) washing the aluminum foil after the second treatment with water, placing it in a 10wt% phosphoric acid solution at a temperature of 50°C for 120s, and then heat treating it at 450°C for 130s.

[0061] (5) The aluminum foil after heat treatment was placed in a 2wt% diammonium phosphate solution for the following three treatments, and then dried at 200°C to obtain an anodized aluminum foil, wherein the temperature of the following three treatments was 90°C, the time was 8min, the voltage was 105Vf, and the current density was 0.05A / dm 2 .

[0062] Performance Testing

[0063] Specific volume: According to EIAJ RC-2364A standard method, the specific volume tester was used for measurement. The test results are shown in Table 1.

[0064] Hydration resistance: The samples obtained in the examples and comparative examples were kept in pure water at 100°C for 12 hours, and the voltage rise time and reaching voltage were measured according to the Tr / Vt test method. The measurement results are shown in Table 1.

[0065] Table 1 Performance test results

[0066]

[0067] From the data analysis, it can be seen from Examples 1-4 in Table 1 that the anodized aluminum foil obtained by the low-pressure formation method of the present invention for reducing the boost time after hydration has a relatively excellent withstand voltage and specific capacity at a voltage of 105V, and has excellent hydration resistance, with a relatively short boost time after 1h and 6h of hydration treatment.

[0068] It can be seen from Example 2 and Comparative Examples 1-3 that the present invention improves both the capacity and hydration resistance of the final aluminum foil by adopting three phosphoric acid treatments in the post-treatment part of the original chemical formation process and controlling the concentration of the phosphoric acid solution to be gradually reduced during the phosphoric acid treatment. This is probably because when the aluminum foil is treated with the method of the present invention, the aluminum oxide film formed on its surface is more compact, the number of micropores in the oxide layer is reduced, and the penetration of water is reduced.

[0069] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A low-pressure formation method for reducing the pressure rise time after hydration, characterized in that: The following steps are involved: S1: The aluminum foil is subjected to primary chemical forming, secondary chemical forming, tertiary chemical forming, quaternary chemical forming, quinary chemical forming, and VI chemical forming in sequence; S2: After the six-stage chemical foil is washed with water, it is placed in a phosphoric acid solution at 40-60°C for 60-180s. After washing with water, it is placed in a 2wt%-10wt% phosphate solution for the next treatment; S3: washing the aluminum foil after the last treatment with water and placing it in a phosphoric acid solution at 40-60°C for 60-180s, and then placing it in a 2wt%-10wt% phosphate solution for the second treatment; S4: washing the aluminum foil after the second treatment and placing it in a phosphoric acid solution at 40-60°C for 60-180s, and then heat treating it at 400-500°C for 80-180s. S5: placing the heat-treated aluminum foil in a 2wt%-10wt% phosphate solution for the following three treatments, and then drying at 150-250° C. to obtain an anodized aluminum foil; The concentration of the phosphoric acid solution in step S2 is 18-25wt%; the concentration of the phosphoric acid solution in step S3 is 8-15wt%; the concentration of the phosphoric acid solution in step S4 is 3-6wt%; The temperature of the latter treatment in step S2 is 70-90°C, the time is 5-15min, the voltage is 20-200Vf, and the current density is 0.05-0.15A / dm 2 ; The temperature of the second treatment in step S3 is 70-90°C, the time is 5-15min, the voltage is 20-200Vf, and the current density is 0.05-0.15A / dm 2 ; The temperature of the last three treatments in step S5 is 70-90°C, the time is 5-10min, the voltage is 20-200Vf, and the current density is 0.05-0.15A / dm 2 .

2. The low-pressure formation method for reducing the post-hydration pressure rise time according to claim 1, characterized in that: In step S1, the first-stage formation liquid is 1wt%-15wt% ammonium adipate solution, the second-stage formation liquid is 7wt%-15wt% ammonium adipate solution, the third-stage formation liquid is 5wt%-15wt% ammonium adipate solution, the fourth-stage formation liquid is 2wt%-10wt% ammonium adipate solution, the fifth-stage formation liquid is 2wt%-10wt% ammonium adipate solution, and the sixth-stage formation liquid is a mixed solution of ammonium adipate and phosphate; the temperature of the formation liquids is 60-80°C.

3. The low-pressure formation method for reducing the post-hydration pressure rise time according to claim 2, characterized in that: In the mixed solution of ammonium adipate and phosphate, the mass percentage of ammonium adipate is 2wt%-10wt%, and the mass percentage of phosphate is 1wt%-7wt%.

4. The low-pressure formation method for reducing the post-hydration pressure rise time according to claim 1, characterized in that: The primary formation time in step S1 is 5-10 min, and the current density is 0.10-0.30 A / dm 2 The secondary formation time is 5-15min, and the current density is 0.10-0.25A / dm 2 The time for the three-stage formation is 7-20 minutes, and the current density is 0.10-0.25A / dm 2 The time for the fourth stage formation is 7-20min, and the current density is 0.10-0.25A / dm 2 The five-stage formation time is 10-25min, and the current density is 0.10-0.25A / dm 2 The six-stage formation time is 15-35min, and the current density is 0.10-0.15A / dm 2 .

5. The low-pressure formation method for reducing the post-hydration pressure rise time according to claim 1, characterized in that: The voltage of the formation is 20-200Vf.

6. The low-pressure formation method for reducing the post-hydration pressure rise time according to claim 1, characterized in that: The phosphate solution is one of ammonium dihydrogen phosphate solution, diammonium hydrogen phosphate solution, sodium dihydrogen phosphate solution, disodium hydrogen phosphate solution, potassium dihydrogen phosphate solution, and dipotassium hydrogen phosphate solution.

Citation Information

Patent Citations

  • Formation method of low-voltage formed foil and prepared low-voltage formed foil

    CN113322454A

  • Chemical synthesis method for anodic foil oxide film acid resistance

    CN101235527A